2020
DOI: 10.3389/fmicb.2020.00114
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Polyester Hydrolase From the Marine Bacterium Pseudomonas aestusnigri – Structural and Functional Insights

Abstract: Biodegradation of synthetic polymers, in particular polyethylene terephthalate (PET), is of great importance, since environmental pollution with PET and other plastics has become a severe global problem. Here, we report on the polyester degrading ability of a novel carboxylic ester hydrolase identified in the genome of the marine hydrocarbonoclastic bacterium Pseudomonas aestusnigri VGXO14 T. The enzyme, designated PE-H, belongs to the type IIa family of PET hydrolytic enzymes as indicated by amino acid sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
171
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(176 citation statements)
references
References 70 publications
2
171
0
3
Order By: Relevance
“…S1). Eight of these CEs were first described by Martínez-Martínez et al (17), one CE was identified by Hajighasemi et al (18), one CE was identified recently by Bollinger et al (26), and 15 CEs were newly identified in this study. Of the CEs used in this study, 16 CEs were recovered from genome libraries after naive screening; additionally, 9 CEs were identified through genome sequence searches.…”
Section: Resultssupporting
confidence: 55%
“…S1). Eight of these CEs were first described by Martínez-Martínez et al (17), one CE was identified by Hajighasemi et al (18), one CE was identified recently by Bollinger et al (26), and 15 CEs were newly identified in this study. Of the CEs used in this study, 16 CEs were recovered from genome libraries after naive screening; additionally, 9 CEs were identified through genome sequence searches.…”
Section: Resultssupporting
confidence: 55%
“…Νon-biodegradable, alipharomatic polyesters such as PET and PEF can be hydrolyzed by specific enzymes [ 126 , 127 ]. PEF with different Mws was successfully hydrolyzed by Cutinase 1 from Thermobifida cellulosilytica , opening the possibility for the functionalization and recycling of monomers, as FDCA and its oligomers were released during incubation [ 128 ].…”
Section: Biodegradationmentioning
confidence: 99%
“…This article is protected by copyright. All rights reserved Purification of PtEst1 was performed by immobilized metal ion affinity chromatography (IMAC) followed by size exclusion chromatography (SEC) as described earlier [28], with minor modifications. The lysis buffer for IMAC was used without addition of imidazole (20 mM Na2HPO4 pH 7.4, 500 mM NaCl) and the washing buffer was used with 10 mM imidazole (20 mM Na2HPO4 pH 7.4, 500 mM NaCl, 10 mM imidazole).…”
Section: Accepted Articlementioning
confidence: 99%